Language, Photography and Sign. On the Semiotic Status of Images and Objects - Vasilyeva, Ekaterina V. (Actual Problems of Theory and History of Art, 2018)
The article is devoted to the study of the principles of the meaning and the formation of values in photography and the realm of language. The goal of this work is to study the principles in the system of photographic images and the structure of language, where a picture reveals the possibility of non-articulated sense and creates the new regalement of an object. The article is also devoted to the aspects of a sign, which is not only the linguistic basis, but the ground of art theories in the 20th century. This study is based on the supposition that the structure of language and the strategy of a snapshot are similar in many questions. But, at the same time, the principles of language and snapshots reveal significant differences. The author suggests that in relation to the object, a picture and language form a duplicate system that corrects perception and forms an independent ideology of values. The researcher points out the difference of the basic strategies of sense — both in a language system and in a photographic image. The snapshot does not have the denotative meaning: the author supposes that photography allows doubting not only the final sense images, but also the result meaning of language. These observations allow us to take a fresh look at the problem of the interaction between an object and meaning in a photographic image. The snapshot and the language significantly correct the representation of an object — in its phenomenological status and in the sense of the hierarchical articulation of a subject. The status of an object changes in the 20th century, as well as the system of values attached to it.